Pengaruh fraksi volume serat terhadap umu - Astika, I Made (Jurnal Energi Dan Manufaktur, 2012)
Weight reducing was one of the focuses in automotive industrial. The leaf spring especially in light vehicle (e.g. solar powered vehicle) can use the composite materials instead of the metal. The excellences of composite are light in weight, high corrosive resistance, high fatigue life, and high elasticity. In the present study, the composite was tested it’s tensile and fatigue strength. The material was composite with Woven Roving fiber and Yucalac 157 BQTN-EX as the matrix. Matrix to fiber ratio was 60:40, 68:32, and 76:24, respectively. The specimens were produced by press hand lay-up. The results showed that the fatigue life increased with fiber volume fraction as seen in the S-N curve. The observed failure modes were fiber debonding, matrix cracking, delamination, and fiber breaking. The combination of these failure modes had significant impact to decreasing of the composite strength and stiffness.
Keywords: Composite, woven roving/polyester, volume fraction, fatigue life